2007
DOI: 10.1017/s0025315407055026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bait collection on Nereis virens populations and macrofaunal communities in the Solent, UK

Abstract: The Solent European Marine Sites contain many tiers of habitat and species conservation, but also high levels of bait collection. Effective management strategies must be founded on up-to-date and locally based information from relevant studies of the impacts; these have been lacking for the collection of Nereis virens, a key bait species. The impacts on macrofauna were assessed through two approaches; (a) undug and dug sites in the Solent were compared over two years of repeat sampling; and (b) monitoring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…Polychaetes are harvested from intertidal flats around the world for their value as saltwater fishing bait (Creaser et al, 1983;Olive, 1993;Beukema, 1995;Cunha et al, 2005;Skilleter et al, 2006;Watson et al, 2007). Most of the 1000 tonnes of worms traded annually are composed of lugworms, Arenicola marina, and sandworms, Neries virens, from the United Kingdom and the Gulf of Maine (Watson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polychaetes are harvested from intertidal flats around the world for their value as saltwater fishing bait (Creaser et al, 1983;Olive, 1993;Beukema, 1995;Cunha et al, 2005;Skilleter et al, 2006;Watson et al, 2007). Most of the 1000 tonnes of worms traded annually are composed of lugworms, Arenicola marina, and sandworms, Neries virens, from the United Kingdom and the Gulf of Maine (Watson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the 1000 tonnes of worms traded annually are composed of lugworms, Arenicola marina, and sandworms, Neries virens, from the United Kingdom and the Gulf of Maine (Watson et al, 2007). There are also 45 tonnes of Diopatra neapolitana harvested each year in the Rio de Aveiro, Portugal, as well as over 100 tonnes of bloodworms, Glycera dibranchiata, dug from the northeast coast of the United States and Nova Scotia (Klawe and Dickie, 1957;Creaser et al, 1983;Cunha et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Annelid worms are often targeted with high accuracy through bait harvesting (Blake 1979, Watson et al 2007, with harvesting efficiency of up to 70% reported in a study of digging for lugworm (Blake 1979). This higher efficiency is reflected in the larger initial reductions following the use of hand-held gears shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1. Furthermore, annelid worms may be sensitive to damage through non-target interactions with harvesting gear (Skilleter et al 2005, Griffiths et al 2006, Watson et al 2007. Baitworm harvesting targets the larger species such as the king ragworm Alitta virens and lugworms Arenicola spp.…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, there is also literature on the impacts of bait digging with the use of rudimentary or mechanized instruments in benthic ecosystems [17][18][19][20]. The economic implications of baitworm activity for fisheries and conservation management in North European coastal areas have been partly addressed [21][22][23].…”
Section: Introductionmentioning
confidence: 99%